2003
DOI: 10.1159/000068332
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen, a Selective Estrogen Receptor Modulator, Reduces Ischemic Damage Caused by Middle Cerebral Artery Occlusion in the Ovariectomized Female Rat

Abstract: Previous work has demonstrated that physiological concentrations of 17β-estradiol can protect the female rat brain against middle cerebral artery occlusion (MCAO)-induced ischemic damage. The present study examined whether therapeutic doses of the clinically relevant selective estrogen receptor modulator (SERM), tamoxifen, can similarly protect the female rat brain against ischemic stroke damage. Adult female rats were bilaterally ovariectomized and implanted subcutaneously with either a placebo or tamoxifen t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 34 publications
3
48
0
Order By: Relevance
“…25 Because tamoxifen affects ischemic brain damage, 26 we postponed MCAO to 6 weeks after tamoxifen treatment. With this regimen, tamoxifen had no effect on the infarct size (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…25 Because tamoxifen affects ischemic brain damage, 26 we postponed MCAO to 6 weeks after tamoxifen treatment. With this regimen, tamoxifen had no effect on the infarct size (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…LY353381.HCl did not affect cerebral blood flow, suggesting a potential direct neuroprotective effect of this SERM in the brain. Additionally, several studies have shown that the SERM, tamoxifen also significantly reduces infarct size in both transient and permanent occlusion/ reperfusion models of cerebral ischemia [40][41][42][43]. Like the raloxifene analogue, the protective effect of tamoxifen was independent of cerebral blood flow changes, indicating a potential direct neuroprotective effect of this SERM in the brain.…”
Section: Cerebral Ischemiamentioning
confidence: 97%
“…Along these lines, work by our laboratory and others has shown that the selective estrogen receptor modulator tamoxifen can significantly reduce infarct size in both transient and permanent occlusion/reperfusion models of cerebral ischemia (7)(8)(9)(10). Kimelberg and colleagues (7) were the first to report a neuroprotective action of tamoxifen after stroke in male animals, an effect later extended to female animals by our laboratory (9). The effect of tamoxifen was shown to be independent of cerebral blood flow changes, indicating a potential direct neuroprotective effect in the brain by tamoxifen.…”
Section: Institute Of Molecular Medicine and Genetics School Of Medimentioning
confidence: 97%
“…pMCAO was used in all experiments, as described previously by our laboratory (9). Briefly, rats were anesthetized by im injection of ketamine/xylazine (60 mg/ml and 8 mg/ml, respectively).…”
Section: Mcaomentioning
confidence: 99%